2013
DOI: 10.1186/1471-2164-14-687
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide transcriptional analysis of two soybean genotypes under dehydration and rehydration conditions

Abstract: BackgroundSoybean is an important crop that provides valuable proteins and oils for human use. Because soybean growth and development is extremely sensitive to water deficit, quality and crop yields are severely impacted by drought stress. In the face of limited water resources, drought-responsive genes are therefore of interest. Identification and analysis of dehydration- and rehydration-inducible differentially expressed genes (DEGs) would not only aid elucidation of molecular mechanisms of stress response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 84 publications
2
30
0
1
Order By: Relevance
“…In Arabidopsis , water in seeds supplies several biochemical reactions during the seed germination, such as water up-taken from outside [53, 56]. At molecular level, drought stress induced genes have been characterized in different plant species including Arabidopsis [14, 15], rice [1618], soybean [19, 20], and other plants [2123]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Arabidopsis , water in seeds supplies several biochemical reactions during the seed germination, such as water up-taken from outside [53, 56]. At molecular level, drought stress induced genes have been characterized in different plant species including Arabidopsis [14, 15], rice [1618], soybean [19, 20], and other plants [2123]. …”
Section: Resultsmentioning
confidence: 99%
“…At cellular and molecular levels, a large number of genes have been reported to respond to drought stress [1113]. Large scale profiling methods like microarray and next-generation sequencing have been demonstrated to estimate the gene expression changes during dehydration process in several model species, such as Arabidopsis [14, 15], rice [1618], soybean [19, 20] and other plants [2123]. These studies have shown that the plant defense against drought stress starts with the perception of water loss, which can trigger the activation of abscisic acid (ABA)-dependent and ABA–independent regulatory systems [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Breeding for wide or specific adaptation across contrasting cropping conditions can be facilitated by: i) progress in the understanding and exploitation of physiological strategies contributing to plant adaptation and stress tolerance (Araújo et al, 2015); ii) the adoption of managed selection environments or phenotyping platforms capable of reproducing the genotype adaptive responses that occur across agricultural regions (Annicchiarico and Piano, 2005); iii) the development of inexpensive screening procedures for tolerance to key stresses [e.g., intrinsic pea tolerance to radiant frost: Shafiq et al (2012)]; and iv) the development of molecular marker-based selection procedures for stress tolerance based on individual quantitative trait loci (e.g., Zhang et al, 2015) or the analysis of individual genes [e.g., via transcriptional analysis: Chen et al, 2013)]; and v) the combination of major-and minor-gene effects into genomic selection models for predicting yield responses in specific cropping conditions (Annicchiarico et al, 2015a). The exploration of marker-based selection for drought tolerance has been remarkably limited in feed legumes, despite the importance of this stress (Araújo et al, 2015).…”
Section: Reviewmentioning
confidence: 99%